(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Consumers and firms are conducting a substantial and rapidly increasing amount of business on the Internet. Many companies have started using the Internet with the aim of cutting marketing costs, thereby reducing the price of their products and services in order to stay ahead in highly competitive markets. The growth of interest in the Internet as a shopping and purchasing medium is fascinating for practitioners and researchers alike. Objectives of the present study is to identify key factors influencing consumer’ of Sonipat district in online shopping purchase behavior and to identify whether different categories of online Sonipat buyers e.g., trial buyers, occasional buyers, frequent buyers and regular buyers perceive website factors and whether these perceptions affect buying behavior in different ways. The research findings indicated that each website factor has a crucial influence on all online buyers’ attitude towards of online purchasing. The results show that majority of the respondents less than 29 years use internet for online shopping. 75 percent respondents are graduation who purchase through online shopping.